The Cytoskeletal Network Regulates Expression of the Profibrotic Genes PAI-1 and CTGF in Vascular Smooth Muscle Cells - Samarakoon, Rohan; Higgins, Paul J (Advances in pharmacology (1990), 2018)
Vascular smooth muscle cells (VSMCs) are subject to changing hemodynamic stimuli that alter cytoskeletal dynamics, cellular architecture, and structure-associated signal transduction. Tensional stress, force application, and structural perturbations are sensed by VSMCs and impact the physiological as well as pathophysiological responses of the vasculature. Microtubule-targeting drugs provide useful tools to analyze cytoskeletal-associated signaling pathways and their linkages to pathological outcomes. Architecture-based controls on a subset of profibrotic genes commonly expressed in vascular disease are highlighted by their frequent induction in mechanically manipulated cells and with associated changes in cytoskeletal dynamics. VSMCs respond to biomechanical cues by activating several kinase cascades, leading to gene reprogramming. It is apparent that a significant fraction of the vast repertoire of signaling intermediates, moreover, are sequestered on the cytoskeletal framework in an "inactive state." Reorganization within these networks due to fluctuating mechanical forces could release these effectors from their cytoskeletal anchors, thus alleviating the "repressive state" resulting in downstream signaling. Indeed, recent findings indicate that microtubule disruption in VSMCs rapidly stimulates pp60 kinase activation and epidermal growth factor receptor (EGFR) transphosphorylation at Y845, a src kinase target residue. EGFR genetic deficiency, pharmacological inhibition of EGFR signaling, or adenoviral delivery of the kinase-deficient EGFR construct effectively blocked colchicine-stimulated expression of two prominent vascular profibrotic genes, plasminogen activator inhibitor type-1 (PAI-1; SERPINE1) and connective tissue growth factor (CTGF; CCN2). Signaling intermediates involved in microtubule collapse-initiated PAI-1/CTGF induction in VSMCs include the MEK/ERK, Rho/ROCK, and SMAD2/3 pathways. This review highlights commonalities and differences in signaling events that facilitate expression of vascular disease-relevant genes initiated as a consequence of loss of microtubular integrity.